V.P.Tsessevich - a way in science - Karetnikov, V. G. (Одеські астрономічні публікації, 2017)
The biography of Vladimir Platonovich Tsessevichj one of the most prominent variable star researches? is briefly presented. The opening talk at the memorial conference ”Variable Stars” (Odessafl September 1-5? 1997) devoted to the 90-th anniversary of the birth of V.P.Tsessevich.